2014
DOI: 10.1159/000363123
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Nongynecological Samples Prepared with Liquid-Based Cytology Medium

Abstract: Objective: Liquid-based cytology of nongynecological specimens is commonly used in cytology laboratories throughout the world and various processing methods, such as ThinPrep and SurePath, have been reported. The cytological features and performance of liquid-based cytology for various cytology specimens, including body cavity fluids, urine, brushing specimens and fine-needle aspiration of various lesions, were reviewed and compared with the experience of our laboratory and the literature published in PubMed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…[6] Hence, interpreting pathologists should be cautious to avoid misinterpretations while reporting FNA prepared using LBC if that is the only methodology employed.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Hence, interpreting pathologists should be cautious to avoid misinterpretations while reporting FNA prepared using LBC if that is the only methodology employed.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the chemical influences of the fixation medium and the physical forces of processing techniques, LBC tends to produce certain cytomorphological alterations and artefacts: smaller cell clusters and sheets and breakage of papillae; more dyscohesive cells; attenuated chromatin details with prominent nucleoli and smaller cell size; intranuclear inclusion is difficult to visualize; altered background matrix in both quantity and quality; aggregation of lymphocytes and markedly decreased number of extracellular particles; and small mononuclear cells, red blood cells, and myoepithelial cells [15].…”
Section: Discussionmentioning
confidence: 99%
“…Pervez et al concluded that the diagnosis of fibroadenoma seems to be most problematic on LBC preparations [19]. Some studies showed a low diagnostic rate compared to CS and false-positive diagnoses while over-classifying fibroadenomas as atypical or suspicious [10][11][12][13][14][15][16][17][18][19]20].…”
Section: Discussionmentioning
confidence: 99%
“…ThinPrep TM might have induced artifacts and cellular morphologic alterations, which influenced diagnostic accuracy. The interpretation requires familiarity with cytological appearance to avoid misdiagnosis [15]. For thyroid lesions the colloid is seen as droplets rather than a diffuse pattern [7].…”
Section: Diagnostic Category For Direct Smear Materialsmentioning
confidence: 99%